Speculative Attacks and Models of Balance of Payments Crises - Flood, Robert; Agenor, Pierre-Richard.; Bhandari, Jagdeep (Washington, D.C. : International Monetary Fund, 1991)
This paper reviews recent developments in the theoretical and empirical analysis of balance-of-payments crises. A simple analytical model highlighting the process leading to such crises is first developed. The basic framework is then extended to deal with a variety of issues, such as: alternative post-collapse regimes, uncertainty, real sector effects, external borrowing and capital controls, imperfect asset substitutability, sticky prices, and endogenous policy switches. Empirical evidence on the collapse of exchange rate regimes is also examined, and the major implications of the analysis for macroeconomic policy discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet